The resilience of the Brazilian Unified Health System is not (only) in responding to disasters - Jatobá, Alessandro; Carvalho, Paulo Victor Rodrigues de (Revista de Saúde Pública, 2024)
Coping with the recent COVID-19 pandemic has shown that the Brazilian Unified Health System (SUS) needs to improve its resilience to handle the rapid spread of communicable diseases while ensuring the necessary care for an aging population with comorbidities and in a vulnerable situation. This article identifies, analyzes, and discusses critical aspects of the resilience of the SUS, calling into question the prevailing focus on the robustness and volume of resources mobilized during the outbreak of major disasters. Recent studies demonstrate that the skills that favor adaptation to unexpected situations emerge from the daily functioning of organizations. Restricting the discussion to the mobilization of structures to respond to adverse events has the effect of limiting their potential, inhibiting the emergence of the transformative, adaptive, anticipatory, and learning skills necessary for the sustainable development of resilience.